BEBERAPA MODIFIKASI PADA ALGORITMA KRIPTOGRAFI AFFINE CIPHER - Dian Eka Wijayanti (Diponegoro University, 2018)
Affine Cipher Cryptography Technique is one of the techniques in classical cryptography which is quite simple so it is very vulnerable to cryptanalysis. Affine cipher's advantage is having an algorithm that can be modified with various techniques. The modifications that can be made to Affine Cipher is to combine Affine cipher's algorithm with other ciphers, replace Affine cipher's key with various functions and matrices and expand the space for plaintext and ciphertexts on Affine cipher. Affine cipher can also be applied to the stream cipher as a keystream generator. This research discusses several modifications of Affine cipher algorithm and performs several other modifications. These modifications are combining Affine Chiper and Vigenere Cipher on , combining Affine, Vigenere and Hill Cipher with invertible matrix applications on . Furthermore, a comparison of the three modifications will be carried out to obtain a new cryptographic method that is more resilient to the cryptanalysis process.